Synthetic approaches to a challenging and unusual structure—an amino-pyrrolidine guanine core - Rippel, Rafael (2020)
Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES (UIDB/50006/2020). Grant number SFRH/BD/136692/2018 from FCT/MCTES.